Packaging Design as Visual Branding for Snack Food Products Produced by KWT Gajah Tani Makmur in Gajahan Village, Colomadu, Karanganyar - Wibowo, Yudi; Yulianto, Arif (Universitas Sahid Surakarta, 2025)
Product packaging is an important for introducing products to the market. Through its packaging, a product can be known and remembered about the product's existence so the brand image is built. Snacks consisting of Fish Crackers and Fish Sticks produced by KWT (Women's Farmers Group) Gajah Tani Makmur do not yet have representative packaging as effective promotional media, because they are only wrapped in plain plastic, so they do not show a strong image about the product being wrapped. The aim of this product packaging design is to create a packaging design for snacks produced by KWT Gajah Tani Makmur so that it has a product image that can encourage strategic product promotion. The packaging design uses a design method with a Design Thinking approach, it means the strategy design focuses on solving problems of producer as design’s client, it is about product promotion problems of KWT Gajah Tani Makmur products. Qualitative data collection was carried out through observation, interviews and literacy studies. Qualitative data analysis is carried out by identifying strengths, weaknesses, opportunities and threats (SWOT). The result is a packaging prototype that shows brand identity that is ready to be used as promotional media. Keywords: Design, Packaging, Visual Branding